2018
DOI: 10.1097/coc.0000000000000301
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Cisplatin Nephrotoxicity in Patients With Head and Neck Cancer Receiving Outpatient Treatment With Concurrent High-dose Cisplatin and Radiotherapy

Abstract: Objectives Cisplatin remains the pivotal chemotherapy in squamous cell carcinoma of the head and neck (SCCHN), with nephrotoxicity considered the dose-limiting toxicity. The purpose of our study was to propose an outpatient high-dose cisplatin (op-HD-cis) protocol aimed at preventing nephrotoxicity and to analyze the results of its utilization in patients with SCCHN treated with concurrent radiotherapy. Methods We retrospectively evaluated 82 SCCHN patients treated with op-HD-cis concurrent with radiotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
38
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 34 publications
10
38
2
1
Order By: Relevance
“…Its soluble form is a 90 kDa molecule (as compared to the membrane bound 104 kDa form) found in the urine of both animals and humans with renal injury. Its presence was associated with AKI in several experimental studies [34,41,42,43,44,45,46,47,48,49,50] and some authors suggest that it may be predictive of cisplatin nephrotoxicity [119,120,121,122,123,124,125,126,127,128,129,130,131,132,133,134,135]. Anti-KIM-1 antibodies have been developed as a potential therapy in neoplasia characterized by KIM-1 overexpression (renal, ovarian, and lung carcinomas) [167,168].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its soluble form is a 90 kDa molecule (as compared to the membrane bound 104 kDa form) found in the urine of both animals and humans with renal injury. Its presence was associated with AKI in several experimental studies [34,41,42,43,44,45,46,47,48,49,50] and some authors suggest that it may be predictive of cisplatin nephrotoxicity [119,120,121,122,123,124,125,126,127,128,129,130,131,132,133,134,135]. Anti-KIM-1 antibodies have been developed as a potential therapy in neoplasia characterized by KIM-1 overexpression (renal, ovarian, and lung carcinomas) [167,168].…”
Section: Discussionmentioning
confidence: 99%
“…KIM-1 levels increased after one-day post-cisplatin administration and this elevation correlated with AKI. Moreover, a form of kidney injury was reported in more than one quarter of patients after the first dose of cisplatin [122,123]. Authors concluded that this biomarker may be able to predict cisplatin-induced AKI [124].…”
Section: Assessment Of Kim-1 In Cisplatin-induced Nephrotoxicitymentioning
confidence: 99%
“…About 13.6% patients with cancer treated with cisplatin develop nephrotoxicity, i.e., acute kidney injury (AKI), which is significantly associated with administrated cisplatin dose [13]. Incidences of nephrotoxicity among head and neck cancer patients receiving cisplatin CRT were 30%-34%, higher than in those with other cancer types [14,15]. Therefore, we evaluated the optimal cisplatin CD for definitive CRT that would maintain efficacy and minimize toxicity among patients with locally advanced NPC in a multicenter setting in Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite its clinical usefulness, CDDP-induced nephrotoxicity is one of the dose-limiting side effects and a major clinical concern; recent retrospective studies have reported that approximately one-third of patients treated with CDDP-based chemotherapy experience acute kidney injury (AKI), even with plausible renoprotective strategies such as co-administration with hydration. 1,2) Therefore, the prediction and prevention of CDDPinduced AKI still remain a challenge.…”
mentioning
confidence: 99%